2020
DOI: 10.3390/ijms21228505
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering the Therapeutic Resistance in Acute Myeloid Leukemia

Abstract: Acute myeloid leukemia (AML) is a clonal hematopoietic disorder characterized by abnormal proliferation, lack of cellular differentiation, and infiltration of bone marrow, peripheral blood, or other organs. Induction failure and in general resistance to chemotherapeutic agents represent a hindrance for improving survival outcomes in AML. Here, we review the latest insights in AML biology concerning refractoriness to therapies with a specific focus on cytarabine and daunorubicin which still represent milestones… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 104 publications
(111 reference statements)
0
12
0
Order By: Relevance
“…Nevertheless, there are certain cohorts with poor prognosis; patients > 60 years with AML demonstrate only 40–60% of remission with overall 24% 5 year survival [ 239 ], while ALL is the leading cause of cancer related deaths among children [ 240 ]. Therapy failure is often associated with drug resistance; in addition to 35–45% of resistant tumors among newly diagnosed cases, relapsed tumors almost never respond to the previously used therapy [ 241 ]. Sometimes the genetic basis of this resistance cannot be found (reviewed in [ 4 ]); hematological malignancies (with the high rate of pediatric cases), especially AML, carry relatively low mutation burden.…”
Section: Drug Resistance and Transcriptional Modulators In Leukemia: Focus On Stemnessmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, there are certain cohorts with poor prognosis; patients > 60 years with AML demonstrate only 40–60% of remission with overall 24% 5 year survival [ 239 ], while ALL is the leading cause of cancer related deaths among children [ 240 ]. Therapy failure is often associated with drug resistance; in addition to 35–45% of resistant tumors among newly diagnosed cases, relapsed tumors almost never respond to the previously used therapy [ 241 ]. Sometimes the genetic basis of this resistance cannot be found (reviewed in [ 4 ]); hematological malignancies (with the high rate of pediatric cases), especially AML, carry relatively low mutation burden.…”
Section: Drug Resistance and Transcriptional Modulators In Leukemia: Focus On Stemnessmentioning
confidence: 99%
“…Sometimes the genetic basis of this resistance cannot be found (reviewed in [ 4 ]); hematological malignancies (with the high rate of pediatric cases), especially AML, carry relatively low mutation burden. In AML, about 40% of resistant tumors show no signs of nonsynonymous coding mutations responsible for resistance [ 241 ].…”
Section: Drug Resistance and Transcriptional Modulators In Leukemia: Focus On Stemnessmentioning
confidence: 99%
“…The treatment of these hematological malignancies has considerably improved in the past years with the recent approval of several novel agents for the treatment of AML, B-ALL, B-CLL and MM, which contributed to expanding the palette of therapeutic options in these diseases [ 1 , 2 , 3 , 4 ]. However, the main reason for treatment failure in a significant proportion of adult patients with leukemias or MM is the occurrence of intrinsic or acquired drug resistance in a subset of malignant cells that is responsible for the development of relapse or refractory disease with a dismal prognosis [ 5 , 6 , 7 , 8 ]. Subsequently, as the development of drug resistance is one of the limiting factors affecting long-term efficacy of anti-leukemic or anti-myeloma drugs, the search for therapies with novel mechanisms of action is an ongoing challenge.…”
Section: Introductionmentioning
confidence: 99%
“…However, they remain restricted to a small number of AML categories. Over time and regardless of the treatment, the tumor microenvironment strongly contributes to promoting the growth and survival of drug-resistant subclones, leading to relapse [ 4 , 5 ]. Several clinical studies have demonstrated that heavy tumor infiltration by MΦs is of poor prognosis: tumor-associated macrophages (TAMs) promote tumor cell growth, resistance to treatment, and escape from immune surveillance [ 4 , 6 ].…”
Section: Introductionmentioning
confidence: 99%